Effect of Stimulation on Breastfeeding Frequency at 1-6 Months of Age - Zahara, Nurfadilah Sahri; Lisviarose; Rizka Mardiya; Nurhidaya Fitria (CV. CENDIKIA JENIUS INDONESIA, 2025)
In Pekanbaru city, 6-month-old infants who received exclusive breastfeeding in 2020 were 53.4%. Problems that affect exclusive breastfeeding to infants include age, education, employment, knowledge, attitudes, family support as well as, maintaining adequate breastfeeding frequency in infants is still a challenge.The stimulation approach to infants can maximize the activity of the vagus nerve and improve food absorption, making babies hungry faster and more often breastfeeding their mothers.This study aims to determine the effect of stimulation on the frequency of breastfeeding at the age of 1-6 months in the independent practice of midwives Bdn. Hasna Dewi and FS, S.Keb in Pekanbaru City. This type of research is a quantitative study with a pre-experimental design approach Pretest-Posttest one Group Design with a population of 15 babies who are breastfeeding. Data were analyzed by univariate analysis and bivariate analysis using the Paired Sample Test. The results of this statistical test obtained a significance value of 0.000 <0.05 which means that Ha is accepted where there is an Effect of Stimulation on Breastfeeding Frequency at the Age of 1- 6 Months in the Independent Practice of Midwife Bdn. Hasna Dewi FS, S.Keb Pekanbaru. Conclusion: an interesting approach in an effort to increase the frequency of breastfeeding in infants is by stimulating routine massage in infants can help babies breastfeed more often. It is recommended to provide regular stimulation to infants as part of daily care. Proper stimulation can support the sensory, motor, cognitive, and social development of infants, so that their growth becomes more optimal.